2021
DOI: 10.3390/en14185689
|View full text |Cite
|
Sign up to set email alerts
|

Pro-Environmental Behaviour in the European Union Countries

Abstract: The purpose of the presented research is to assess pro-environmental behaviour (PEB) in European Union countries in 2009 and 2019. The study used a synthetic measure developed using the TOPSIS (Technique for Order Preference by Similarity to an Ideal Solution) benchmark method. This method enables distinguishing classes and ranks of countries depending on the adopted characteristics. Basic measures of descriptive statistics, i.e., average, standard deviation and the coefficient of variation, were used in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 88 publications
1
25
0
2
Order By: Relevance
“…Morren and Grinstein (2016) mention that many studies have found that countries that have scored high on development have more willingness to pay for environmental products than the countries scoring low on development. Mikuła, Raczkowska, and Utzig (2021) also confirm the positive correlation between pro-environmental behaviour and economic development. They mention that the tendency to desire a better-quality environment increases with increase in income.…”
Section: Theoretical Models and Hypothesissupporting
confidence: 71%
“…Morren and Grinstein (2016) mention that many studies have found that countries that have scored high on development have more willingness to pay for environmental products than the countries scoring low on development. Mikuła, Raczkowska, and Utzig (2021) also confirm the positive correlation between pro-environmental behaviour and economic development. They mention that the tendency to desire a better-quality environment increases with increase in income.…”
Section: Theoretical Models and Hypothesissupporting
confidence: 71%
“…Personal norm represents a moral duty to engage in a particular conduct or refrain from doing so, AC is defined as people's understanding of how pro-social behavior benefits others or their estimations of other things, and the AR shows how responsible people feel about the effects of their pro-social behavior. NAM is regarded as the most influential theory in explanation of proenvironmental decision-making process and behavior (Steg and Nordlund, 2018;Esfandiar et al, 2019Esfandiar et al, , 2022Han, 2021;Mikuła et al, 2021;O'Connor and Assaker, 2021;Gao et al, 2022), households' waste separation (Goh et al, 2022), purchase food (Faletar et al, 2021;Lafontaine et al, 2021;Yang et al, 2021;Le and Nguyen, 2022), waste separation behavior (Esfandiar et al, 2021;Setiawan et al, 2021;Shen et al, 2022), these studies have shown that AR, AC positively affected PN, and AR can be triggered by AC. Accordingly, this research proposes the hypothesis as follows:…”
Section: Theory Of Planned Behaviormentioning
confidence: 99%
“…Having environmental awareness and concerns in parallel with prosocial/intergenerational motivations encourage solar businesspeople toward solar energy development. However, attention to environmental issues, including the concept of environmentalism and modern environmental movements originated in Western Countries, and intensively dealt with (academically) theoretical/empirically by European researchers [48], [49], [50], [51], [52]. Admitting my finding on pro-environmental behaviour in Iran, Jahangir Karami et al conducting a systematic review and meta-analysis, to investigate the pro-environmental behaviour of Iranians (1998-2018) reported that the Iranian citizens have about the average of the global mean index of environmental performance [53].…”
Section: Facilitating the Diffusionmentioning
confidence: 99%